THE STATE OF PRACTICE OF TEACHING THE SUBJECT “MEDICAL BIOLOGY. GENERAL GENETICS” IN HIGHER MEDICAL EDUCATION INSTITUTIONS - Safarov Kholikjon; Khaitov Javohir (Web of Journals Publishing, 2025)
HPV – Human Papillomavirus (HPV — Human Papillomavirus) is a family of viruses that includes about 100 species. Ways of infection. Sexually. You can also get infected through anal and oral sex. These are types 16 and 18 of viruses. In this way, pointed warts appear, which are located on the genitals of women and men. The risk group includes people who frequently change sexual partners.
Keywords: Virus, papillomas, immunity, forms of papillomas.